Transconjunctival sutureless intrascleral intraocular lens fixation using intrascleral tunnels guided with catheter and 30-gauge needles. Issue 11 (8th April 2015) - Takayama, Kohei; Akimoto, Masayuki; Taguchi, Hogara; Nakagawa, Satoko; Hiroi, Kano
Abstract : We invented a new method for fixing an intraocular lens (IOL) in the scleral tunnel without using a wide conjunctival incision. Modified bent catheter needles were used to penetrate the IOL haptics through the sclerotomy sites. The IOL haptics were inserted into 30-guage (G) scleral tunnels guided by double 30-G needles piercing the sclera. All procedures were performed through the conjunctiva without wide incision. The procedure does not require special forceps, trocars or fibrin glue, only catheter and 30-G needles. The aid of an assistant was not required to support the IOL haptic. The procedures were easily learnt based on our previous method. As with other transconjunctival sutureless surgeries, patients feel less discomfort and the conjunctiva can be conserved for future glaucoma surgery. Complications included two cases of vitreous haemorrhage (16.7%), and one case each of postoperative hypotony, and iris capture (8.3%). Astigmatism induced by intraocular aberration was the same as we reported previously. Our method for fixing the IOL into the scleral tunnel is innovative, less expensive, less invasive and quick. This modified method is a good alternative for fixing IOL haptics into the sclera.